What is known about the FTP20 test related to cycling? A scoping review - Mackey, J.; Horner, K. (Journal of Sports Sciences, 2021)
Functional Threshold Power (FTP) in cycling is increasingly used in exercise prescription, particularly with the rise in use of home trainers and virtual exercise platforms. FTP testing does not require biological sampling and is considered a more practical test than others. This scoping review investigated what is known about the 20-minute FTP (FTP20) test. A three-step search strategy was used to identify studies in relevant databases (PubMed, CINAHL, SportDiscus, Google Scholar, Web of Science) and grey literature. Data were extracted and common themes identified which allowed for descriptive analysis and thematic summary. Fifteen studies were included. The primary focus fitted broadly into four themes: reliability, association with other physiological markers, other power-related concepts and performance prediction. The FTP20 test was reported as a reliable test. Studies investigating the relationship of FTP20 with other physiological markers and power-related concepts reported large limits of agreement suggesting parameters cannot be used interchangeably. Some findings indicate that FTP20 may be useful in performance prediction. The majority of studies involved trained male cyclists. Overall, existing literature on the FTP20 test is limited. Further investigation is needed to provide physiological justification for FTP20 and inform use in exercise prescription in a range of populations.